A prospective study of cases with necrotising fasciitis: our experience at a tertiary care teaching hospital - Mittal, S.; Singh, B.; Mittal, R.; Singh, K. (International Surgery Journal, 2017)
Background: Necrotising fascitis is a life-threatening infection involving fascia and necrosis of subcutaneous tissue. The portal of entry usually is trivial trauma. It requires immediate diagnosis and intervention to reduce mortality. The objective of this study was to study clinical profile, predisposing risk factors and to formulate a protocol for management of necrotising fasciitis. Methods: The study was conducted at tertiary care teaching hospital in Punjab, India catering to a semi-urban and rural (agricultural based) population over a period of three years between January 2014 to January 2017. All the consecutive patients who came to the emergency department (ER) of the institute presenting early with clinical features suggestive of NF were included in the study. The study included total 50 cases. The cases were studied in detail according to study plan that included age, sex, clinical features, results of blood and wound cultures, the number of surgical interventions, total duration of hospitalization and the mortality rate. Results: The most common age group was between 40-60yrs and there were 48 males. There was history of trivial trauma or insect bite in majority of cases. Mostly patients presented with bullae formation, induration, edema. Diabetes was the commonest comorbid condition associated. All the patients were thoroughly investigated, swab cultures were taken. Debridements were done followed by grafting. In 10 patients, we could not salvage the limb and 10 patients expired after debridement. Conclusions: Necrotising fasciitis is more common in middle aged males with diabetes. Early diagnosis and aggressive treatment is required to reduce the mortality.